Exploring Relevant Employability Skills 4.0 For University Students’ Readiness in The Work-Based Learning Program - Halili, Siti Hajar; Fathima, Nasreen; Razak, Rafiza (Journal of Technical Education and Training, 2022)
This research discusses employability skills 4.0 for university students' readiness in work-based learning. This research explored relevant employability skills 4.0 for university students' readiness in the work-based learning program. The survey questionnaire consisted of 65 items developed to study the student's readiness to acquire these skills in a work-based learning program. This research obtained 633 respondents from five Malaysian research universities. The association between employability skills and students' readiness for work-based learning was analysed using the PLS-SEM model of SMART-PLS software. Using measurement and structural model analysis, the PLS-SEM found six employability skills communication skills, interpersonal skills, IT skills, problem-solving skills, entrepreneurship skills, and self-management skills. From this analysis, the student's readiness employability 4.0 for the university student's readiness in work-based learning has developed. Further research can explore more significant respondents from public or private universities, including postgraduate students in the survey